2008
DOI: 10.1002/qj.194
|View full text |Cite
|
Sign up to set email alerts
|

The propagation and diurnal cycles of deep convection in northern tropical Africa

Abstract: ABSTRACT:The propagation and diurnal cycle of organized convection in northern tropical Africa are examined using five years (1999)(2000)(2001)(2002)(2003) of digital infrared imagery for May-August. Reduced-dimension techniques are used to document the properties of cold clouds -proxies for deep convection and precipitation. Large-scale environments are diagnosed from global analyses.Organized convection in Africa consists of coherent sequences or episodes which span an average distance of about 1000 km and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
132
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 71 publications
33
132
1
1
Order By: Relevance
“…As mentioned previously, MCSs often travel faster than AEWs, and therefore life-cycle characteristics could be aliased to wave regimes other than the formative and decay stages. Despite this limitation, occurrence frequency results were consistent with previous studies (most of which concentrated on genesis/lysis of MCS with respect to AEW phase) that have found that deep convection occurs east of AEW troughs near the continental sites and west of and in the trough near the coast and Atlantic (Carlson, 1969;Payne and McGarry, 1977;Reed et al, 1977;Diedhiou et al, 1999;Fink et al, 2006;Kiladis et al, 2006;Laing et al, 2008). Fink and Reiner (2003) and Laing et al (2008), primarily using microwave and infrared observations for squall line and deep convective tracking, respectively, found a large fraction of systems were not associated with any AEW phase.…”
Section: Precipitation Feature Characteristicssupporting
confidence: 90%
“…As mentioned previously, MCSs often travel faster than AEWs, and therefore life-cycle characteristics could be aliased to wave regimes other than the formative and decay stages. Despite this limitation, occurrence frequency results were consistent with previous studies (most of which concentrated on genesis/lysis of MCS with respect to AEW phase) that have found that deep convection occurs east of AEW troughs near the continental sites and west of and in the trough near the coast and Atlantic (Carlson, 1969;Payne and McGarry, 1977;Reed et al, 1977;Diedhiou et al, 1999;Fink et al, 2006;Kiladis et al, 2006;Laing et al, 2008). Fink and Reiner (2003) and Laing et al (2008), primarily using microwave and infrared observations for squall line and deep convective tracking, respectively, found a large fraction of systems were not associated with any AEW phase.…”
Section: Precipitation Feature Characteristicssupporting
confidence: 90%
“…Both systems are characterized by a marked diurnal cycle with development of convection after 1200 UTC, a maximum around 1800 UTC and a rapid decrease from 0600 to 1200 UTC. This is in agreement with the convection cycle evaluated from the MSG climatology over Africa presented in Laing et al (2008).…”
Section: Cloud-top Brightness Temperaturesupporting
confidence: 91%
“…A realistic diurnal cycle is reproduced with generation of convection at 1200 UTC on each simulation day and a maximum around 1800 UTC. From CTBT maps at 1400 UTC (not shown), it is possible to observe that convection initiates on the lee side of the Darfur mountains, in agreement with the analyses of Laing et al (2008) and Mekonnen et al (2006).…”
Section: Cloud-top Brightness Temperaturesupporting
confidence: 82%
See 2 more Smart Citations